CT-based quantitative evaluation of the efficacy after radiofrequency ablation in patients with benign thyroid nodules. (1st January 2020) - Choi, Yangsean; Jung, So-Lyung; Jang, Jinhee; Shin, Na-Young; Ahn, Kook-Jin; Kim, Bum-soo
Abstract: Objective: The purpose of this study was to evaluate the usefulness of CT for quantitative assessment of the neck structures after RFA in patients with benign thyroid nodules. Materials and methods: This single-center, retrospective cohort study included 38 patients with benign thyroid nodules who had received RFA and had available pre- and post-treatment CT images. Changes in the tracheal anteroposterior (AP)/transverse diameter ratio, cross-sectional tracheal area, midline deviation of the trachea, and anterior neck angle after RFA were quantitatively measured using CT. Volume reduction rates (VRRs) for the thyroid gland and nodules were measured using CT and US, respectively, and the intraclass correlation coefficient (ICC) was calculated. The paired Wilcoxon signed-rank test was used to compare pre- and post-treatment CT-based measurements, and univariate linear regression analysis was performed to determine the association of VRR with the mean delivered radiofrequency energy, number of RFA sessions, and initial thyroid volume. Results: After RFA, the tracheal AP/transverse diameter ratio and midline deviation were significantly decreased while the tracheal area and anterior neck angle were significantly increased (all, p  < 0.001). The thyroid volume reduction was also significant (VRR, 42.1% ± 21.1%, p  < 0.001), with moderate consistency between the CT-based thyroid VRR and US-based nodule VRR (ICC = 0.68, 95% confidence interval = 0.38–0.83, p  < 0.001). The mean delivered radiofrequency energy ( p  = 0.565), number of RFA sessions ( p  = 0.209), and initial thyroid volume ( p  = 0.363) showed no significant association with VRR. Conclusion: CT-based quantitative assessments may be useful for evaluating improvements in the neck structures after RFA for benign thyroid nodules.